2005
DOI: 10.1111/j.1048-891x.2005.15014.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and management of uterine sarcoma patients treated at the Tom Baker Cancer Centre

Abstract: The purpose of this study was to evaluate patients with uterine sarcoma from Southern Alberta to assess patterns of care and outcomes associated with treatment by a multidisciplinary team. Using the Alberta Cancer Registry database, charts of all uterine sarcoma patients treated between 1988 and 1997 in Southern Alberta were extracted. The majority of patients underwent definitive surgery. Adjuvant treatments were performed in selected patients at the discretion of the multidisciplinary tumor board. Demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 37 publications
4
8
0
Order By: Relevance
“…Our data were consistent with Benito et al study which found CS in 48% and LMS in 22% (Benito et al, 2009). Contrast with other studies in Thailand, most common type are LMS .Other previous studies reported different findings, with similar frequency of CS and LMS (Kelly and Craighead, 2005;Koivisto et al, 2008;Park et al, 2008;Durnali et al, 2012). The small number of cases in each study might have exaggerated the different proportion of each uterine sarcoma type.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Our data were consistent with Benito et al study which found CS in 48% and LMS in 22% (Benito et al, 2009). Contrast with other studies in Thailand, most common type are LMS .Other previous studies reported different findings, with similar frequency of CS and LMS (Kelly and Craighead, 2005;Koivisto et al, 2008;Park et al, 2008;Durnali et al, 2012). The small number of cases in each study might have exaggerated the different proportion of each uterine sarcoma type.…”
Section: Discussionsupporting
confidence: 90%
“…The small number of cases in each study might have exaggerated the different proportion of each uterine sarcoma type. Nevertheless, our study and all other previous studies found ESS or AS as the least common constituting only 10-30% (Kelly and Craighead, 2005;Koivisto et al, 2008;Park et al, 2008;Benito et al, 2009;Durnali et al, 2012). Our patients' mean age of 54 years was within the range of 50 to 62 years reported in other studies (Livi et al, 2003;Park et al, 2008).…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations